Implementing Career Counseling and Guidance: The Challenge in Indonesia - Nisa Novia Avien Christy; Masine Slahanti (CV. Uruboros Publishing Group, 2025)
Counselling remains a relatively new and evolving discipline in developing nations. The political landscape in developing nations is frequently unstable. Indonesia is a developing country with a scarcity of career counseling and guidance services. This study contributes comprehensive information regarding the primary challenges of career counseling and guidance in Indonesia. This study employed a literature review methodology, utilizing documentary analysis for data collection. The compiled documents present the findings of journal research and theoretical studies pertinent to national and international publications from 2012 to 2022. The key issues and challenges are as follows: 1) The provision of professional human resource and system support; 2) Technology development; 3) Cultural factors; 4) The prominence of behavioristic counseling is exceedingly dominant. This study also concludes with recommendations for the advancement of counseling and guidance in Indonesia.